Numerical simulation of the three edge bearing test of steel fiber reinforced concrete pipes - Ferrado, Facundo Luis; Escalante, Mario Raúl; Rougier, Viviana Carolina (Asociación Argentina de Mecánica Computacional, 2016)
Historically, steel has been the material chosen to improve the tensile behaviour of concrete. Nowadays, the trending of replacing the traditional reinforcement bars with short and slender ﬁbers randomly distributed in the mass concrete, is growing. This composite material made essentially of common concrete reinforced with discrete ﬁbers is called steel ﬁber reinforced concrete(SFRC). In this work the mechanical behaviour of SFRC pipes is studied, simulating the diametral compression test called three edge bearing test by means of a 2d model in plane strain state. The SFRC is considered as a homogeneous material and its behaviour is represented through some damage - plasticity model (concrete damage plasticity) which takes into account the progressive reduction in the values of the elastic constants due to plastic strain and damage by means of a stiffness degradation variable. The model assumes that the main two failure mechanisms of the concrete are tensile cracking and compressive crushing, thus, the tensile and compression response is characterized through differentiated uniaxial stress-strain curves. This representation, although simpliﬁed, captures the most important features of the concrete response. The equations are solved with a commercial computational package. In addition, and as an alternative for the same problem, a case is addressed in which the SFRC is considered as an equivalent homogeneous material too, although a coupled plastic-damaged model is used where the coupling between plasticity and damage is achieved through a simultaneous solution of the plastic and the damage problem. Finally is presented a modiﬁed coupled damaged plasticity model that comes from a modiﬁcation of the LublinerOller yield criterion from the adoption of a yield function of second degree in the components of the stress tensor. For the coupled damage plasticity the contribution of the ﬁbers is considered through the classic mixture theory according to it is performed a modiﬁcation of the elastic constants depending on the volumetric contribution of the ﬁbers. Here, the problem is solved using the non-linear ﬁnite elements code PLastic Crack dynamic (PLCd) The validity of the numerical tool is performed comparing the results of the simulation with experimental data existing in the literature.
Keywords: Concrete pipes; SFRC; Plasticity; Nonlineality material